ANALISIS NILAI TAMBAH PRODUK ROTAN DI ROTANCRAF SMKN-2 KECAMATAN KATINGAN HILIR KABUPATEN KATINGAN - Susanti, Susanti; Pordamantra, Pordamantra; Revi Sunaryati (J-SEA (JOURNAL SOCIO ECONOMIC AGRICULTURAL), 2018)
This study aims to find out the general description of the rattan processing business in the study area, knowing the management of rattan processing into furniture in the study areaand knowing the magnitude of the analysis of added value produced from rattan processing into furniture in the study area.This research was carried out in the Rotancraf processing industry of SMKN-2 Katingan Hilir, Katingan Regency, Jenderal Sudirman No. 2 Kilometer 8 Kereng Humbang Kasongan. Site selection is done purposive based on certain considerations adjusted to the research objectives on the grounds that the location of the research is the only rattan processing industry in the Katingan Hilir District. Data sources used in this study include primary data and secondary data. Primary data is data data obtained from the results of direct interviews with respondents and assisted with a questionnaire. Secondary data are data obtained from other sources such as journals, research reports, theses, internet sites, textbooks and from several government agencies related to research. The results of this study indicate that the added value obtained for rattan chairs is Rp.2.561.000 (two million fivehundred sixty one thousand rupiah). While the added value for rattan bags is Rp.2.648.000(two million six hundred forty eight thousand rupiah).